Femur fractures and hemorrhagic shock: Implications for point of injury treatment. Issue 10 (October 2022) - Mitchnik, Ilan Y.; Talmy, Tomer; Radomislensky, Irina; Chechik, Yigal; Shlaifer, Amir; Almog, Ofer; Gendler, Sami
Highlights: Clinical practice guidelines (CPG) recommendations for prehospital leg traction splinting are inconsistent. Contrary to traditional teaching, severe hemorrhagic shock due to femur shaft fractures (FSF) is rare. Blood loss in casualties with FSF may be attributed to other concurrent injuries which require more urgent attention. Open FSF injuries may present as thigh bleeding which is difficult to control and may benefit from leg traction splinting. Prehospital CPG should stress the use of leg traction splints for suspected FSF injuries with severe shock or difficult bleeding. Abstract: Background: Femur shaft fractures (FSF) are perceived as potentially life-threatening injuries due to significant blood loss. However, these injuries are rarely the sole cause of hemorrhagic shock. Clinical practice guidelines for the prehospital management of FSF are inconsistent, especially concerning the use and timing of traction splinting which is postulated to reduce bleeding. We sought to understand the association between FSF and shock, and identify risk factors for shock among casualties with FSF. Methods: This is a retrospective analysis of trauma casualties treated by Israeli Defense Forces (IDF) medical teams between the years 2000–2020 and suffering from isolated FSF. Prehospital data from the IDF-Medical Corps Trauma Registry was merged with hospitalization data from the Israeli National Trauma Registry. Isolated FSF was analyzed by excluding casualties with an Injury Severity Score ≥ 16 and an Abbreviated Injury Scale ≥ 3 in other anatomical regions. Shock was defined as systolic blood pressure ≤ 90 mmHg and/or heart rate ≥ 130 beats per minute. A case series review was performed for casualties in shock with isolated FSF injuries. Multivariable logistic regression was performed to assess for injury characteristics associated with shock. Results: During the study period, we identified 213 patients with FSF (4.9%) of which 129 were isolated injuries. Overall, 9.9% and 26.3% of casualties had concurrent thoracic and abdominal injuries, respectively. Most FSF were due to motor vehicle accidents (60.1%) and shock was present in 17.1%. In isolated FSF patients, gunshot and explosive injury mechanisms were prevalent (65.0%) with severe shock being present in 8.5%. Open fractures were present in 72.7% of isolated FSF patients in shock. Open FSF injuries were characterized by prehospital bleeding which was difficult to control. In a multivariable logistic regression model, severe concomitant injuries were associated with increased odds of shock. Conclusions: Shock rarely presents when FSF is the primary injury. Such casualties predominantly suffer from open FSF which may present as difficult to control thigh bleeding. Our findings do not support urgent prehospital leg traction splinting which may result in delayed evacuation to definitive care. Casualties with shock and FSF should be investigated for other sources of bleeding. Leg traction splinting should be reserved for suspected FSF injuries with shock or persistent thigh bleeding.